2005
DOI: 10.1070/pu2005v048n11abeh005804
|View full text |Cite
|
Sign up to set email alerts
|

The ambipolar trap

Abstract: PACS. 68.00 -Surfaces and interfaces; thin films and whiskers.PACS. 68.30 -Dynamics of solid surfaces and interface vibrations.Abstract. -For the Au(ll0)-reconstructed surface we present a comparison of surface phon02modes measured with inelastic He-scattering and calculated from first principles. For the r point use of bulk force constants does not explain the observed vibrational modes, while the microscopic first principles results give good agreement with the experiment. In contrast to recent results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Finally, a series of studies has shown that open magnetic traps with reasonably improved axial confinement are completely consistent with reactorlevel fusion projects with power gain factor Q ≫ 1. Improvement of axial confinement can be achieved, for example, through the use of ambipolar plugs [6,7] or multimirror endsections [8]. The most attractive from engineering and physical standpoint are axisymmetric magnetic mirrors.…”
mentioning
confidence: 99%
“…Finally, a series of studies has shown that open magnetic traps with reasonably improved axial confinement are completely consistent with reactorlevel fusion projects with power gain factor Q ≫ 1. Improvement of axial confinement can be achieved, for example, through the use of ambipolar plugs [6,7] or multimirror endsections [8]. The most attractive from engineering and physical standpoint are axisymmetric magnetic mirrors.…”
mentioning
confidence: 99%
“…In Ref. [5], in the case of an axisymmetric open trap, it was shown that the region of robust shell stabilization exists for the plasma with hot ions and β exceeding some threshold value [6]. Therefore, the optimization of the shell stabilization plates position is the relevant issue.…”
Section: Diamagnetic Fieldmentioning
confidence: 99%
“…AMBAL-M experiment Historically, the first experiment with mirror-machine arranged in Budker Institute was the ambipolar trap AM-BAL with quadrupole anchor cells and later on the axially symmetric AMBAL-M experiment [12]. The main goals of the AMBAL-M experiment were the study of the ambipolar plasma confinement and achieving the MHD stability of hot plasma in axisymmetric geometry using the halfcusp anchor cells.…”
Section: Lessons Learned From Previous Generation Of Magnetic Mirror Devices At Binpmentioning
confidence: 99%